2021
DOI: 10.1094/pbiomes-01-21-0005-sc
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbes Influence Host Circadian Clock Function

Abstract: The circadian clock is an important determinant of fitness that is entrained by local conditions. Aside from abiotic factors, individual pathogenic soil bacteria affect circadian clock function in plant hosts. Yet, in nature, plants interact with diverse microbial communities, and the effect of complex communities on clock function remains unclear. In Arabidopsis thaliana and its wild relative, Boechera stricta, we used diverse rhizosphere inoculates and host genotypes to test the effect of complex rhizosphere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Recent work in A. thaliana and its wild relative Boechera stricta demonstrated that the rhizosphere microbes also influence host circadian rhythms. In plants where the rhizosphere microbial community was disrupted, the length of the circadian period was extended, lasting longer than 24 h, suggesting a role for the microbial community in regulating host circadian rhythms [ 20 ].…”
Section: Interplay Between Host and Symbiont Diel Cyclesmentioning
confidence: 99%
“…Recent work in A. thaliana and its wild relative Boechera stricta demonstrated that the rhizosphere microbes also influence host circadian rhythms. In plants where the rhizosphere microbial community was disrupted, the length of the circadian period was extended, lasting longer than 24 h, suggesting a role for the microbial community in regulating host circadian rhythms [ 20 ].…”
Section: Interplay Between Host and Symbiont Diel Cyclesmentioning
confidence: 99%
“…It is well documented that host clock can influence rhizosphere microbial community (Hubbard et al ., 2018; Lu et al ., 2021; Newman et al ., 2022). Similarly, the rhizosphere microbial community affects the host clock function (Hubbard et al ., 2021). These studies suggest there is a bidirectional rhythmic interaction between plants and their rhizomicrobiome (Xu & Dodd, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the microbial communities inhabiting the rhizosphere of wild‐type, clock mutant, and clock gene‐overexpressing Arabidopsis has revealed differences between the rhizomicrobiome community structure of these genotypes (Hubbard et al., 2018 , 2021 ; Newman et al., 2022 ; Staley et al., 2017 ). Collectively, these studies imply a role for the circadian oscillator in root metabolite release, because exudation shapes rhizomicrobiome community structure (e.g.…”
Section: Circadian Regulation Of Root Exudationmentioning
confidence: 99%
“…Such investigations will benefit from non‐targeted root exudate profiling approaches to obtain a holistic assessment of circadian involvement in the release of different metabolite classes, because identification and quantification of various compound types is sensitive to the technical approach used (reviewed in Pantigoso et al., 2021 ; Salem et al., 2022 ). Assess relationships between diel or circadian exudation cycles and wider rhizosphere processes : Whilst researchers have started to analyze the effect of core circadian oscillator genes on rhizomicrobiome composition (Hubbard et al., 2018 , 2021 ; Newman et al., 2022 ; Staley et al., 2017 ), work is needed to directly assess rhythmic metabolic interactions between root exudates and rhizosphere microbial communities (Figure 2b,c ). One approach to studying these potential rhythmic interactions could be to use microfluidics (Massalha et al., 2017 ).…”
Section: Circadian Regulation Of Root Exudationmentioning
confidence: 99%